Optimizing The Role of Bhabinkamtibmas on Minimizing the Spread of The Covid-19 Virus With Kampung Tangguh Nusantara Program in Polres Tarakan District - Boas Dekison (Police Studies Review, 2021)
This research was motivated by the high spread of the Covid-19 virus in Polres Tarakan district. The level of material and moral losses caused by the increasing spread of the Covid-19 virus can cause a national development and health deficit, so it is important for the Police to put forward preventive efforts in order to reduce it. Therefore, a study was conducted which aims to determine the description of the implementation and the factors that influence Kampung Tangguh Nusantara Program which is carried out by Bhabinkamtibmas Satbinmas Polres Tarakan. This research was conducted using a descriptive analysis research method and a qualitative approach. Kampung Tangguh Nusantara program analyzed using Surat Kapolda Kaltara Nomor : B/660/VI/REN.4.1./2020 number 3 point (a) is considered not optimal because only a few parts of the assessment indicators have been fulfilled. The factors that become obstacles include internal and external factors consisting of the field of human resources, the field of facilities and infrastructure, the field of budget, support for other functions in the police, support across agencies, and the support of the residents of Kelurahan Karang Anyar. Based on the results of these studies, the authors provide suggestions according to the concepts and theories used, namely the concept of Kampung Tangguh Nusantara, the theory of 4M management elements and POAC, so that the development and restructuring of the management organization of Kampung Tangguh Nusantara is carried out based on the Job Description of each member. number of Bhabinkamtibmas personnel, the existence of written provisions of the HTCK between functions and related institutions. This includes improving the control and supervision of Satbinmas budget, holding Binmas Dikjur, implementing the concept of reward and punishment, reforming the presentation material, and research related to the implementation of the Kampung Tangguh Nusantara Program from a perspective other than the police institution.